Organized crime in Ostia. A theoretical note (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
Even if only recently public opinion is focalizing on Ostia, this criminal context had been very problematic since the 1970s. Here several criminal organizations cohabit, fight and shared power and areas of influence. But what made very particular this municipality is the presence of very strong and well embedded local mafias (autochthonous criminal groups that adopt mafia model, without any link with traditional organizations). These groups had been developed also in others Italian region, but in Rome seems to be permanent and stronger (sometime also stronger than traditional mafias). So, this paper proposes an analysis of local mafias embedded model in a non-traditional territory, and in particular it is presented a case study on Ostia.Keywords: Territory, local mafias, Ostia, non-traditional areas, mafia model